Osteocalcin and Abdominal Aortic Calcification in Hemodialysis Patients: An Observational Cross-Sectional Study - Jia, Fengyu; Wang, Suxia; Jing, Ying; Zhao, Hanhui; Rong, Peng; Zhang, Hongbin; Lu, Wenting; Xue, Yan; Sun, Gang (Frontiers in Endocrinology, 2021)
Objectives To investigate the serum level of osteocalcin (OC), also known as bone Gla protein, in maintenance hemodialysis (MHD) patients and its correlation with abdominal aortic calcification (AAC). Methods From July 2017 to February 2020, we enrolled 108 adult MHD patients. Routine fasting blood laboratory tests were performed before the start of the second hemodialysis in a week. Abdominal aortic calcification score (AACs) was assessed within 1 month. Pearson correlation and Logistic regression were used to analyze the data. Results The OC level was 231.56 (25.92,361.33) ng/ml, elevating significantly in this group of MHD patients. It had a positive correlation with serum phosphorus (r = 0.511, P = 0.001), intact parathyroid hormone(iPTH) (r = 0.594, P = 0.0001), fibroblast growth factor 23(FGF23) (r = 0.485, P = 0.003) and a negative correlation with age(r = -0.356, P = 0.039). Based on the AACs, patients were divided into two groups. Serum OC level were higher in patients with AACs≥5 (p=0.032). A multiple logistics regression analysis revealed that age (odds ratio [OR]1.14, P=0.005) and OC(OR=1.10, P=0.008)were risk factors for high AACs(≥5). Conclusion The study implicated that OC elevated significantly in this group of MHD patients.OC is positively correlated with phosphorus, iPTH, FGF23, and a negative correlation with age. OC was a risk factor for vascular calcification in this study, but this study did not classify osteocalcin as c-OC and unOC. Whether unOC is associated more directly with vascular calcification requires further study.